UJI KONDUKTIVITAS TERMAL KOMPOSIT POLIESTER FILLER SERBUK KAYU ULIN (EUSIDEROXYLON ZWAGERI) - Bustomi, Fakhdilah; Ghofur, Abdul (Universitas Lambung Mangkurat, 2021)
To find out the best thermal conductivity value on the volume fraction of ironwood polyester filler composite (Eusideroxylon Zwageri) and to determine the effect of the number of voids on the value of the thermal conductivity of the ironwood polyester composite composite (Eusideroxylon Zwageri). This study uses an experimental method by conducting thermal and microstructure conductivity tests to see the many voids that have formed. The object in this study uses ironwood powder. Data analysis techniques in this study used descriptive data analysis which is describing research results graphically in a table. Input parameters in analyzing data include variations in the mixture of ironwood powder and resin (20% -80%, 25%: 75% and 30%: 70%), and 100% resin. The results of the study of the effect of the volume fraction of ironwood polyester composite composites on the value of thermal conductivity decreased with increasing volume of ironwood powder with the smallest thermal conductivity value at 30% volume fraction of ironwood powder : 70% polyester resin matrix that is 0.041 W/moC. The influence of the amount of voids on the thermal conductivity value of ironwood polyester composite composites can be seen that the more voids the smaller the thermal conductivity values. The number of voids along with the increasing volume of ironwood powder.